PENGARUH VARIABEL MEDIASI VALUE-BASED SELLING TERHADAP KINERJA INSURANCE ADVISOR - MARIA AUGUSTINE GRACIAFERNANDY (Universitas Sarjanawiyata Tamansiswa, 2022)
In the insurance industry, the customer is the determinant of the success or failure of this business. Insurance advisors play an important role as a liaison between insurance companies and insurance seekers who will contribute to the prosperity of the organization. Customer-oriented insurance advisor will be able to achieve good sales performance. Various literatures say that value-based selling is an effective sales method. This is because the value will make it easier for customers to make a purchase decision. The main data of this study were obtained from questionnaires filled out by 100 insurance advisors. The responses received will be analyzed using the SEM AMOS 23 program. The results of this analysis will explain the causal relationship between the variables developed in this study. Hypothesis testing has proven that there is a positive relationship between customer orientation and value-based selling. Customer orientation can significantly increase value-based selling. Another hypothesis test proves that there is a positive and significant relationship between value-based selling and the performance of insurance advisors. It is concluded that customer-oriented insurance advisors will always create value-based selling methods so that they will have a positive impact on improving their performance.